Variables associated to intensive care unit (ICU)-mortality among patients admitted to surgical intensive care unit in Ethiopia: a retrospective observational study - Misgan Mulatie Zewudie; Debas Yaregal Melesse; Tesera Dereje Filatie; Mulualem Endeshaw Zeleke (BMC Anesthesiology, 2023)
Abstract Background The present study aimed to assess variables associated to ICU-mortality among patients admitted to surgical intensive care unit in Ethiopia. Methods A Hospital-based retrospective follow-up study was conducted on all patients who were admitted to the surgical intensive care unit. Data were extracted from patients’ charts with a pretested data extraction tool, entered into Epi-data 4.6.0, and analyzed with STATA- 14. Bivariate and multivariate Cox proportional hazards regression models were fitted. Results Of the total study participants (388), 148 (38.1%) patients admitted to the surgical intensive care unit died during the follow-up period with a median survival time of 11 days. Potassium level < 3.5 mmol/L (adjusted hazard ratio ( AHR): 3.46, 95% CI (1.83 6.55), potassium level > 5.0 mmol/L (AHR:2.41, 95% CI (1.29–4.51), hypoxia (AHR:1.66, 95% CI (1.10–2.48), Glasgow Coma Scale (GCS) score < 9 (AHR: 4.06, 95% CI (1.51–10.89), mechanical ventilation (AHR:12, 95%CI (3–45), absence of thromboprophylaxis (AHR:10.8,95% CI (6.04–19.29), absence of enteral feeding (AHR:3.56, 95% CI (2.20–5.78) were variables associated with ICU-mortality among patients admitted to surgical intensive care unit. Conclusions The overall ICU-mortality of patients admitted to our surgical intensive care unit was higher compared to patients admitted to similar intensive care unit in developed countries. The variables associated to ICU-mortality among patients admitted to surgical intensive care unit were abnormal serum potassium level, lower GCS score, mechanical support, hypoxia, absence of thromboprophylaxis, and enteral feeding.